Analisis Penanganan Penyandaran Kapal untuk Menghindari Container Delay - Mahsunah E. Rahayuningsih; Candra O. Putri; Mar’atus Sholikah; Deri Herdawan; Marselia Marselia (SAINTARA, 2023)
PT Indo Container Lines is an international transportation firm that offers import/export, stevedoring, freight forwarding, and agency services. The investigation of ship berthing handling at PT Indo Kontainer Sarana BUP Multipurpose Terminal is the primary focus of this study. There are a number of underlying issues that need to be addressed in this study, including: the nature of the process by which container delays occur during ship berthing; the nature of the factors that contribute to such delays; the nature of the impact that results from such delays; and the nature of the agent's efforts to overcome such delays. The purpose of this study is to find ways to reduce the time it takes for ships to dock, which would otherwise cause the consignee to wait longer for their shipment and result in higher Terminal Handling Charges (THC). Ship berthing procedures and container loading and unloading operations at storage facilities for stacked cargo are included. This study employs the descriptive research approach and gathers its data via observation, interviews, documentation, and a review of the relevant literature. According to the study's findings, the problem with the MV Icon Corintus's berth might be solved if the ships, agents, and loading/unloading procedures all worked together more efficiently. This is done so that BUP PT Indo Kontainer Sarana doesn't have to pay extra to deal with ships parked at the port, disassemble containers, and stack them. Agents are responsible for docking ship operations, such as maintaining damaged engines or defective loading and unloading equipment.